Manejo agronómico en época seca para la producción forrajera del pasto Brachiaria decumbens - Valle Garzón, Jordy Smith (2025)
The main objective of this research was to understand the agronomic management of Brachiaria decumbens for forage production during the dry season. The methodology was based on information from current documents such as research articles, virtual libraries, blogs, and websites, which allowed for a better analysis of the opinions and ideas of stakeholders regarding agronomic management during the dry season for Brachiaria decumbens forage production. Regarding the results, agronomic management of pastures seeks to optimize their productivity and persistence by maintaining forage balance and nutrient recycling. To estimate grass availability in pastures, methods such as fertilization, cultural practices, and weed, pest, and disease control are required. In conclusion, it was found that grasses of the Brachiaria genus exhibit good adaptation, yield, and high nutritional value for animal feed, provided that appropriate agronomic management is implemented, based on fertilization, cultural practices, and weed, pest, and disease control. This optimizes productivity and persistence, maintaining forage balance and nutrient recycling. The most appropriate seeding density for Brachiaria decumbens grass with seeds is between 5 and 8 kg/ha, with a cutting age of 75 days producing the highest yields during the dry season.